In vitro treatment of Acacia saligna (Labill) trees seeds dormancy. (Albayan Scientific Journal, 2023)
Acacia saligna is an ornamental tree that adapts ecologically to Al-jabal Al-akhdar region, However, it suffers from physical dormancy so can't germinate naturally. so this study was conducted to improve germination under conditions laboratory, using different treatments, included treatment of scarified mechanical, scarified with soaking in distilled water 24 hours, scarified with soaking in distilled water 48 hours, treatment of soaking in Hydrochloric acid at concentrated (20, 40 and 60%) for a period of 20 minutes, treatment of soaking in hydrogen peroxide at concentration  6% for a periods of (12, 24 and 48) hours, treatment of soaking in distilled water for a period of (24, 48 and 72) hours, and finally treatment of soaking in hot water for a period of (15, 30 and 60) minutes. Results showed the superiority of treatment of soaking in hydrogen peroxide periods of 12, 24 hours on all treatments with a germination percentage of (91.1, 84.4%), and the lowest averages germination time of (3.5, 3.6 days) respectively, followed by scarified with soaking in distilled water 24 hours and scarified mechanical, while distilled water treatment was unsuccessful and consume a long time to obtain germination. The study concluded that soaking in hydrogen peroxide Effective method in breaking dormancy trees seeds Acacia saligna, and scarification technique is impractical due to small size of seeds.
Keywords: Acacia saligna; breaking dormancy; different treatments